Entry of Herpes Simplex Virus Mediated by Chimeric Forms of Nectin1 Retargeted to Endosomes or to Lipid Rafts Occurs through Acidic Endosomes - Gianni, Tatiana (American Society for Microbiology, 2004)
Herpes simplex virus (HSV) enters cells by fusion with target membranes, commonly the plasma membrane. In some cells, including CHO cells expressing the nectin1 or herpesvirus entry mediator receptors, entry occurs through an endocytic route. We report the following results. (i) When expressed in J cells, nectin1 and HVEM mediated a pathway of entry insensitive to endosome acidification inhibitors. (ii) A chimeric nectin1 receptor competent for endosomal uptake by fusion of the nectin1 ectodomain with the transmembrane sequence and cytoplasmic tail of the epidermal growth factor receptor (EGFR1) (nectin1-EGFR1) and chimeric nectin1 sorted to lipid rafts by a glycosylphosphatidylinositol anchor mediated endocytic entry blocked by the early endosome inhibitor wortmannin and by the endosome acidification inhibitors bafilomycin and NH(4)Cl. (iii) Entry mediated by nectin1-EGFR1 was selectively inhibited by AG1478, a tyrosine phosphorylation inhibitor that targets the EGFR1 cytoplasmic tail and blocks the signaling pathway that culminates in clathrin-dependent uptake of the receptor into endosomes. We draw the following conclusions. (i) The same receptor may initiate different routes of infection, depending on the cell in which it is expressed. Hence, the cell is a determinant that controls whether a given receptor initiates a plasma membrane or an endocytic route of entry. (ii) Receptors whose physiology involves uptake into endosomes or sorting to lipid rafts are suitable to serve as HSV receptors. (iii) Structural features of the receptors are additional determinants that control whether HSV entry occurs at the plasma membrane or at endosomes. These findings are relevant to studies of HSV retargeting to specific receptors.